1998
DOI: 10.1046/j.1440-1819.1998.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of non‐primary motor areas during a complex finger movement task revealed by functional magnetic resonance imaging

Abstract: We examined the brain activation induced by a complex ®nger movement task using functional magnetic resonance imaging (fMRI) with echo planar imaging (EPI). Imaging planes were set up for the observation of non-primary motor areas. Among ®ve normal males examined, four subjects naive to the task showed activations in contralateral primary and supplementary motor areas and the ipsilateral superior anterior part of the cerebellar hemisphere. Also, the bilateral premotor areas and the contralateral ventrolateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Nevertheless, subcortical brain activation was reported in earlier fMRI studies. 4,7,9,14,18,19 Beyond these technical impairments, subcortical regions might be a major focus in schizophrenia research regarding the influence of neuroleptic medication and of schizophrenic disorder as well. In psychiatric disorders, morphological and functional abnormalities in subcortical regions might be of major importance regarding treatment and symptomatology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, subcortical brain activation was reported in earlier fMRI studies. 4,7,9,14,18,19 Beyond these technical impairments, subcortical regions might be a major focus in schizophrenia research regarding the influence of neuroleptic medication and of schizophrenic disorder as well. In psychiatric disorders, morphological and functional abnormalities in subcortical regions might be of major importance regarding treatment and symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…Although, in principle, fMRI provides adequate resolution to image the basal ganglia at the spatial scale of the nuclei, activating these nuclei with fMRI has proven to be difficult. 4,9,14,[18][19][20] In patients with schizophrenia, neuroimaging data provide evidence of cortical and subcortical abnormalities. In particular, the interhemispheric interaction was found to be disturbed.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary with fMRI, the estimated blood oxygenation level dependent (BOLD) contrast reveals neuroplastic changes in the activated cortex (Wu et al, 2005 ). Motor tests, for instance finger tapping induce activation within a wide sensorimotor network (Moriyama et al, 1998 ) thus enabling evaluation of afferent-induced effects beyond the motor cortex (Christova et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although, in principle, fMRI provides adequate resolution to image the basal ganglia at the spatial scale of the nuclei, activating these nuclei with fMRI has proven to be difficult 5 . Moriyama et al found only an occasional activation of the contralateral ventrolateral thalamus, but no activation of putamen or globus pallidus 18 . Using a fingertapping paradigm an activation of globus pallidus was found by Izawa et al 11 and Reichenbach et al 7 Differences in the activation during externally and self‐paced sequences of arm movements were found by Menon et al 9 …”
Section: Introductionmentioning
confidence: 95%
“…5 Moriyama et al found only an occasional activation of the contralateral ventrolateral thalamus, but no activation of putamen or globus pallidus. 18 Using a fingertapping paradigm an activation of globus pallidus was found by Izawa et al 11 and Reichenbach et al 7 Differences in the activation during externally and self-paced sequences of arm movements were found by Menon et al 9 Using a simple fingertapping paradigm several studies with psychiatric patients demonstrate discrepant results. Some studies of motor activation have reported decreased activation in schizophrenia in the cortical motor regions and normal activity in others.…”
Section: Introductionmentioning
confidence: 99%